Analisis Pengaruh Literasi Keuangan terhadap Kesejahteraan Suplier Teri Nasi di Desa Dungkek Kabupaten Sumenep - Rachman Hakim; Mohammad Amir Furqon; Gazali Gazali; Farid Farid (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Dungkek Village is an area with very abundant potential for anchovies. However, so far, fishermen and suppliers of anchovies have often experienced problems with capital. Using quantitative research, this research will measure the level of financial literacy and its impact on the welfare of anchovy suppliers in Dungkek Village, Sumenep Regency. The total research sample (sample size) was 42 research respondents. This research will be carried out in 2022 in Dungkek Village, Sumenep Regency. Education level, financial literacy, and work experience will be independent variables. Meanwhile, the welfare of rice anchovy suppliers is used as the dependent variable. Multiple linear regression analysis will be used to determine the influence of work experience, education level, and financial literacy on the welfare of anchovy suppliers based on a recapitulation of questionnaire answers obtained from respondents. Based on the research results, the level of work experience has the most dominant influence in improving supplier welfare. Meanwhile, the level of education and financial literacy also have a big influence. The effect of financial literacy is significantly positive on the welfare of rice anchovy suppliers. Higher financial literacy can improve the welfare of rice anchovy suppliers.